From Nearly Zero Water Buildings to Urban Water Communities: The Need to Define Parameters to Support the New Paradigms - Sara Bona; Armando Silva-Afonso; Ricardo Gomes; Carla Pimentel-Rodrigues; Fernanda Rodrigues (Applied Sciences)
In the context of freshwater scarcity, effective water resource management is essential. This study explores techniques to optimise the use of local water sources and promote conservation, proposing a model to balance the supply and demand of non-potable water in urban environments. The model serves as an alternative or complement to public water supplies, particularly in drought-prone regions. Through a qualitative analysis of national and international regulations, specifications, and technical standards, this research identifies key trends in the use of alternative water sources and highlights knowledge gaps in urban water management, which are addressed through the proposed model. The study emphasises the transition from Nearly Zero Water Buildings (NZWBs) to Urban Water Communities (UWCs) as a sustainable and resilient solution, integrating decentralised water management approaches and resource recovery from wastewater. Additionally, a case study in a Portuguese urbanisation area illustrates the application of these principles and assesses their potential in real-world scenarios. The findings contribute to the development of comprehensive guidelines and public policies for sustainable urban water management, supporting the implementation of decentralised and integrated solutions that enhance resilience, water security, and resource efficiency.